Social Background Effect on The Choice of The Students Language - Wahyuni, Rani Sri (Universitas Suryakancana, 2026)
This article discusses the influence of social background on the choice of language varieties used in interactions in the STT Wastukancana Purwakarta campus environment.. This social background in question includes the following factors: Like the origin of the region, the level of education of parents, the work of parents, and the social environment. This study uses a descriptive qualitative approach with survey methods and interviews with 50 STT Wastukancana Purwakarta student respondents from various study programs. Data were analyzed through reduction, presentation, and drawing conclusions based on sociolinguistic theory. The results of this study indicate that differences in social background greatly affect the variety of languages used by students, both in the context/formal and non-formal situations. Students from the urban environment and highly educated tend to use standard Indonesian in formal situations, while students from rural environments more often use mixed languages, namely regional languages and non-standard Indonesian language. These findings confirm that the variety of languages among students is not only determined by the situation of communication, but also by social factors that form language habits. This research is expected to contribute to the development of sociolinguistic studies that highlight the dynamics of language among tertiary students, especially in the context of higher education in the region.Keywords: language variety; social background; students